Sustainability of Green Design Mosque in Cyberjaya - Danish, Muhammad; Shukri, Sharyzee Mohmad; Taib, Idris (MAJ - Malaysia Architectural Journal, 2023)
The sustainable design aims to improve the building’s overall performance in regard to the surrounding natural elements by reducing negative impacts on the environment as well as the health and comfort of the users of the building. The primary goals of sustainability are to limit non-renewable resource use, eliminate waste, and promote healthy, productive ecosystems. The intention of this paper is to evaluate the approaches of Raja Haji Fi-Sabillilah Mosque to achieve a Platinum Award in Green Building Index. The method of this paper is the study of the elements of sustainability by an in-depth literature review, sources from interviewing the Project Designer, and Site Observation. This paper discusses on how the mosque adapt to the environmental issue, elements of design that works to correlate with nature and lessen its impact towards it. The implementation of sustainable design the building incorporates are sustainable material of construction, cross ventilated, green rooftop, Low-E Glass, Water Body, Solar Energy, Screening Façade, Structural Canopy, Passive Dome Design, and a green Landscape. Findings collected help conclude that the sustainable application implement onto the Mosque not only reduces the heat gain by the Mosque by means of the Overall Thermal Transfer Value (OTTV), it also works with the environmental factor to benefit the Mosque, using it to its advantage achieving peak Sustainability, achieving a Platinum rating Green Building Index.